Interacting with Cage: Realising classic electronic works with contemporary technologies. Issue 3 (16th November 2015) - Gurevich, Michael
Abstract : At a time when tape music, which obviated the need for performers by eliminating interpretation after composition, was becoming the dominant paradigm for electronic music, John Cage, motivated by his inchoate aesthetic of indeterminacy, radically reimagined electronic music that 'treats machines as things to perform with'. In the 1950s and 1960s, Cage employed electronic technologies in place of musical instruments in concert music, but also reframed the creation of tape music by following a score to be a performative act. Although Cage idealised a liberal approach to performance practice and maintained a modernist, utilitarian attitude towards technological progress, his actions and scores reflect allegiance to the 'work concept' (Goehr1992 ). Twenty-first-century performers of Cage's electronic music are challenged to address the seemingly paradoxical imperatives of technological progressivism and creative interpretation with fidelity to a work embodied in a score. This article discusses efforts to reconcile these forces in contemporary realisations using the interactive technologies of three of Cage's classic electronic works. The development of interactive performance interfaces in response to musical requirements of a score is presented as an important but overlooked model for the development of new interfaces for musical expression.